Phytochmical constituents and nutrient evaluation of Zingiber officinale - Al-hadad M.A; Al-Samarrai, R.R; Ahumaih, M.J (Tikrit Journal of Pure Science, 2023)
Zingiber officinale has been analyzed for the main phytochemical composition, nutrient and mineral composition.The phytochemical screening of chemical constituents of the plant showed that ginger contains sterols , flavonoids, glycosides amino acids , carbohydrates , taninat terpenoids ,saponins.